Analisis Komparatif Tingkat Kepuasan Mahasiswa antar Jurusan di Politeknik Negeri Padang terhadap Pelayanan Pendidikan - Zahara; Eliyanora; Septriani, Yossi; Afni, Zalida (Jurusan Akuntansi Politeknik Negeri Padang, 2015)
This study is aimed at identifying studentsâ€™ satisfactory levels toward educational services provided by Politeknik Negeri Padang (PNP) and further determine whether there is a gap between their expectation and actual services that they receive. We define educational services as services provided by lecturers, administration staffs, and managerial officers. It is also included studentsâ€™ perception on teaching-enhanced tools. The measurement of studentsâ€™ satisfactory level is conducted using 5 variables, i.e reliability, responsiveness, assurance, empathy and tangible. Moreover, these variables are operationalised through several questions. All answers of these questions use likert scale within the range of 1 to 4. The score of studentsâ€™ satisfactory level of PNP is further converted to the standard of Quality Assurance Services for government organizations, referring to KEPMENPAN No. KEP/25/M.PAN/2/2004. This study finds that educational services provided by PNP is reasonably good. There is a gap between studentsâ€™ expectation level and actual services that they receive. On average, the score for their expectation is 3.71 whilst it is 2.59 for actual services (using the scale from 1 to 4). Of all departments in PNP, Accounting and Machinery Engineering has the lowest gap, 1.07 and 0.95 consecutively. Meanwhile, the highest gap occurs for Civil and Electrical Engineering, with score of 1.21. Overal, based on the Standard of Quality Assurance Services of KEPMENPAN No: KEP/25/M.PAN/2/2004, we conclude that studentsâ€™ satisfactory level for PNP is in â€œBâ€ category, indicating that the performance of its educational service is â€œgoodâ€.